Meningkatkan Kepercayaan Diri Siswa Melalui Kegiatan Ekstrakurikuler - Agnesita Sekar Arumdani (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
The purpose I made this article is learning to know about extracurricular activities for the elementary school. This article is based on my opinion, analysis scientific, and theoretical review. The result from my thought is can be concluded that to increase student’s confidence the school can do that with extracurricular activities. Program extracurricular divided into two types there are extracurricular required (scouting) and extracurricular preference. Strategy the teacher to increase student confidence gives them reinforcement and a developmental approach.